2015
DOI: 10.1563/aaid-joi-d-13-00219
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Bone Augmentation Using Autogenous Block Grafts and Particulate Xenograft in the Severe Atrophic Maxillary Anterior Ridges: A Cone-Beam Computerized Tomography Case Series

Abstract: The aim of the present study was to use cone-beam computerized tomography (CBCT) to assess horizontal bone augmentation using block grafts, harvested from either the iliac crest (IC) or mandibular ramus (MR) combined with particulate xenograft and a collagen membrane for in the severe maxillary anterior ridge defects (cases Class III-IV according to Cadwood and Howell's classification). Fourteen healthy partially edentulous patients requiring extensive horizontal bone reconstruction in the anterior maxilla wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
1
48
0
1
Order By: Relevance
“…An important factor when using biomaterials in the maxillary sinus has to do with compaction [13][14]. LuminaPorous ® must fill the space neither excessively nor insufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…An important factor when using biomaterials in the maxillary sinus has to do with compaction [13][14]. LuminaPorous ® must fill the space neither excessively nor insufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as those conducted by Block et al, 8 Maiorana et al, 16 Cosso et al 17 and Monje et al, 15 all of which assessed the importance of this type of association, are unanimous in stating that this technique leads to less bone resorption, thereby providing surgeons with more confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Monje et al 15 used computed tomography scans to assess the increase in thickness of 19 block bone grafts harvested from the iliac crest or mandibular ramus, and associated with heterogeneous graft. The authors concluded that this technique is predictable and favors implant placement.…”
Section: -20mentioning
confidence: 99%
See 1 more Smart Citation
“…If the residual alveolar ridge is too thin to place dental implant, bone grafting is the only choice for successful dental implant rehabilitation (1,2). Anterior maxillary area is critical site for dental esthetics.…”
Section: Introductionmentioning
confidence: 99%